2019
DOI: 10.2334/josnusd.18-0130
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics analysis for the preoperative prediction of airway changes after maxillomandibular advancement surgery

Abstract: Maxillomandibular advancement surgery is useful for treatment of sleep apnea. However, preoperative analysis and evaluation to facilitate decision-making regarding the direction and distance of maxillomandibular movement has primarily consisted of morphological analysis; physiological function is not evaluated. To improve preoperative prediction, this study used fluid simulation to investigate the characteristics and effects of airway changes associated with maxillomandibular movement. A one-dimensional model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Our previous studies [ 19 , 20 , 23 ] demonstrated that CFD simulations could largely reproduce patients’ actual respiratory flow dynamics. This study suggests that CFD can be used to analyze respiration air flows in areas that cannot be measured by rhinomanometric methods, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies [ 19 , 20 , 23 ] demonstrated that CFD simulations could largely reproduce patients’ actual respiratory flow dynamics. This study suggests that CFD can be used to analyze respiration air flows in areas that cannot be measured by rhinomanometric methods, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…CT scans of the nose, sinuses, and upper airway of participants were obtained with 1-mm-thick 3D-CT image slices preoperatively and at the 1-year postoperative follow-up; 3D-CT scans were evaluated using the same methodology as in our previous study [ 19 ]. To measure airway geometries of all cases in the following condition, X-ray CT (X-CT) scanning measurements were conducted.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations